New land mollusk fauna from Serra da Capivara, Piauí, Brazil, with a new genus and five new species (Gastropoda: Orthalicoidea, Streptaxidae, Subulinidae) - Simone, Luiz Ricardo L.; Casati, Rafael (Zootaxa, 2013)
Five new species and one new genus are described from the Serra da Capivara, Piauí, Brazil, a region of semi-dry, Caat-inga environment. The described taxa are: Odontostomidae: 1) Clinispira insolita, n. gen. n. sp., possessing strange spire inclination and aperture approaching to the shell apex, it looks closely related to Anostoma, Tomigerus and Biotocus; 2) Cyclodontina capivara n. sp., with well-developed axial ribs and 6 teeth at peristome; 3) Anctus prolatus n. sp., very elon-gated, with aperture lacking teeth; Simpulopsidae: 4) Rhinus gilbertus n. sp., somewhat elongated and relatively well-sculptured; Streptaxidae: 5) Streptartemon molaris n. sp., possessing a very large basalis tooth at peristome. Two subulin-ids are also reported from the region: 6) Beckianum beckianum (Pfeiffer, 1846), a population with peculiar pointed shell apex and well-developed axial sculpture; 7) Lamellaxis cf. gracilis (Hutton, 1834), a wide-ranged species that merits fur-ther investigation. These descriptions show how scanty is our knowledge on northeast Brazilian malacofauna and may raise efforts for its preservation.